Poly(ethylene glycol)dimethacrylate – nanofibrillated cellulose bionanocomposites as injectable hydrogel for therapy of herniated nucleus pulposus patients - Prihartini Widiyanti; Mochamad Arsyal Amali; Aminatun (Journal of Materials Research and Technology, 2020)
The highest disease caused by low back pain is herniated nucleus pulposus (HNP) where nucleus pulposus (NP) protrudes out through the annulus fibrosis. Injectable hydrogel is a method to restore NP function with minimal invasive surgery. Variation concentration of NFC were studied in detail toward affects on PEGDMA (poly(ethylene glycol)dimethacrylate):NFC hydrogel mechanically and injectability. The characteristics of PEGDMA and nanofibrillated cellulose (NFC) based injectable hydrogels through the photoinitiator Irgacure 2959 in the formation of hydrogels with variations composition 1:0; 1:0.25; 1:0.5; 1:0.75. In the morphological test on NFC a fibre with a diameter of 100 nm was formed from the results of electrospinning on ethyl cellulose (EC). The FTIR showed of photopolymerization of the conjugation bond between Irgacure 2959 and PEGDMA producing C-C at a frequency of 1349.20 cm−1. Swelling test used phosphate buffer saline (PBS) fulfilled the standard at a variation of 1:0.25; 1:0.5; and 1:0.75, 87.07%, 84.84% and 80.42% respectively. Viscosity test in the injectability of hydrogels showed a result of 73.67 dPa.s. The compressive strength test obtained good results in samples 1:0.75 showed a result of 3.42 kPa. In vitro injection model showed increasing of NFC concentration indicates the gel state when released from agarose will be less rupture. PEGDMA/NFC hydrogel biocomposite has the potential to be applied as an injectable hydrogel for the treatment of HNP patients based on the results.